Die Entwicklung der Lohnstruktur im ostdeutschen Transformationsprozeß - Viktor Steiner; Patrick A. Puhani (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
The development and the structure of the distribution of hourly wages in Eastem Germany between 1990 and 1994 are analysed on the basis of the German Socio-Economic Panel (GSOEP). To this end, we first calculate standard measures of inequality and decompose the changes in the inequality of hourly wages into the changes between and within socio-economic groups. The economic factors discussed in the literature as infIuencing the distribution of hourly wages are summarized and analysed by way of empirical wage equations. In the discussion of our results, we focus on the human capital effects of the transition process and the impacts of the industrial structure on wages.
Keywords: J31; J24; P51; 330; Lohnstruktur; Lohndifferenzierung; Neue Bundesländer